SIMPLIFIED HATCHERY TECHNIQUE FOR MASS PRODUCTION OF PENAEID PRAWN SEED USING FORMULA FEED - Mohamed, K H; Muthu, M S; Pillai, N N; Pandian, S K (Indian Journal of Fisheries, 2011)
A techaique for large-scale production of penaeid prawn seed using a drymicroparticulate formula feed, NPCL-17, is described. The details of preparing thefeed which is compounded from inexpensive, locally available raw materials suchas groundnut oil cake, fish meal, dried mantis shrimp, prawn waste and tapiocaand fortified with vitamins and minerals are given. The larvae are grown in outdoortanks filled with 2 m' of seawater, filtered through 60-micron mesh nyloboltcloth. The daily ration of formula feed is offered in 4 equal instalments at 6hourly intervals and the larval tanks are vigorously aerated. Apart from providingnutrition for the larvae, the feed, under the influence of sunlight, helps to createa natural ecosystem conducive for their survival. The easy-to-dispense dry feedhas greatly simplified the larval rearing procedures and has given an average survival*rate of 66.7% from nauplius to postlarva. The rationale of the feeding schedulesand the particle size of the feed offered are discussed in the light of thechanges taking place in the functional morphology of the feeding appendagesduring larval development